Pharmacological effects of Clinacanthus nutans Lindau and its potential cosmeceutical values: a comprehensive review - Zamery, Muhammad ‘Izzuddin; Mohammed Ahmed, Abdul Kareem; Khalid, Kamarul Ariffin; Ab. Hadi, Hazrina (PharmaInfo Publications, 2020)
Clinacanthus nutans is largely cultivated in Asia tropical regions and predominantly native to Malaysia, Indonesia, Thailand and China. It is an important species from the Acanthaceae family and regarded as one of the primary contributor to the medicinal plants. This plant had been traditionally used as treatment of poisonous snake bites, skin rashes, dysentery, haematoma, rheumatism and injuries. Public Health Ministry of Thailand had used it as the primary therapy for lesion treatment due to virus. Phytochemicals recovered from this plant are chlorophyll derivatives, flavones, isoflavones and sulphur-containing glucosides. They exhibited various pharmacological effects such as anti-herpes simplex virus, ntiinflammatory and anti-cancer via various mechanisms. They also can potentially be exploited as the main ingredients in the cosmetic products including the lightening, anti-aging as well as anti-acne products since it exhibited the presence of compounds that had been proven to have anti-tyrosinase activity (melanin reduction), anti-oxidants (protection from UV radiation), anti-microbial towards Propionibacterium acnes and anti-inflammatory activities